WORD-FINDING DIFFICULTIES, VERBAL PARAPHASIAS, AND VERBAL DYSPRAXIA IN 10 INDIVIDUALS WITH FRAGILE-X-SYNDROME - Spinelli, M.; Rocha, ACD; Giacheti, C. M.; Richiericosta, A. (Wiley-Blackwell, 1995)
Speech/language disorders are common in the fragile X syndrome. [Howard-Peebles, 1979: Am J Hom Genet 31:214-222; Renier et al., 1983: J Ment Defic Res 27:51-59; Sparks, 1984: Birth Defects and Speech-Language Disorders, pp, 39-43; Hanson et al., 1986: Am J Med Genet 23:195-206]. Verbal paraphasias have been considered a rare feature and word-finding difficulties have seldom been reported. Here we report on ten Brazilian patients who were evaluated for speech/language disturbances and found that word-finding difficulties were present in 50% of the cases, which is a slightly higher frequency than that of clear dyspraxia. We suggest, therefore, that word-finding difficulties and verbal dyspraxia can be a common feature within the spectrum of this syndrome. Additional speech findings are discussed. (C) 1995 Wiley-Liss, Inc.
Keywords: FRAGILE X SYNDROME; FRA-X; VERBAL DYSPRAXIA; WORD-FINDING DIFFICULTIES; LANGUAGE DISORDERS; SPECIFIC LANGUAGE DISORDERS